Epidemiology and resistance mechanisms of tigecycline- and carbapenem-resistant Enterobacteriaceae in China: a multicentre genome-based study - Yan, Lixin; Ma, Tingting; Wang, Wen; Cai, Zhen; Du, Hong; Chen, Zhongju; Han, Renru; Guo, Yan; Li, Gang; Jia, Wei; Tao, Jia (Frontiers in Microbiology, 2025)
ObjectivesTo elucidate the molecular epidemiology of tigecycline and carbapenem-resistant Enterobacteriaceae isolates and mechanisms of tigecycline resistance.MethodsWe gathered 31 unduplicated strains of tigecycline-resistant Enterobacteriaceae from six hospitals nationwide. Antimicrobial susceptibility testing, phenotypic detection, and PCR identification were performed first, followed by homology analysis using MLST and PFGE. Conjugation transfer experiments using resistance gene plasmids were carried out, and the conjugates’ growth curves were examined. All strains were sequenced using the Illumina HiSeq technology, and we identified a strain KP28 carrying a complete gene cluster tmexCD2-toprJ2. Then, its plasmid was further constructed using the PacBio platforms to complete the frame. The genetic connection of the tmexCD2-toprJ2 gene cluster carried by KP28 was established using core genome analyses.ResultsAll 31 tigecycline-resistant Enterobacteriaceae strains (TG-CRE) were multidrug resistant. PFGE classified strains of CRKP, CRECL, and CRKAE into 16 distinct spectra, 6 distinct spectra, and 3 distinct spectra. MLST results showed a high concentration of ST11 in CRKP strains and a predominance of ST116 in CRECL strains, suggesting possible clonal transmission or selective dominance. The findings of the plasmid conjugation assay revealed that three strains expressing carbapenem resistance genes were effectively transmitted to the recipient cell E. coli EC600. WGS data revealed that these 31 strains include 79 resistance genes, with one strain (KP28) carrying the whole tigecycline resistance gene cluster, tmexC2D2-toprJ2. This resistance gene is contained in a large IncHI5 plasmid, which is difficult to transfer.ConclusionThe overall carriage rate of the tmexC2D2-toprJ2 gene cluster was found to be low among the five Chinese hospitals investigated. Conversely, tet(A) mutations were present in most of the strains. Bacteria with the carbapenem resistance genes blaKPC and blaNDM are vulnerable to horizontal transmission. Increasing the risk of transmission of antibiotic-resistant genes.